2020
DOI: 10.48550/arxiv.2010.07330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photon Emission from Circular Equatorial Kerr Orbiters

Delilah E. A. Gates,
Shahar Hadar,
Alexandru Lupsasca

Abstract: We consider monochromatic and isotropic photon emission from circular equatorial Kerr orbiters. We derive analytic expressions for the photon escape probability and the redshift-dependent total flux collected on the celestial sphere as a function of emission radius and black hole parameters. These calculations crucially involve the critical curve delineating the region of photon escape from that of photon capture in each emitter's sky. This curve generalizes to finite orbital radius the usual Kerr critical cur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…which holds in the limit where B eq → 0, even though (42) will not be well-defined. One can also show that this relation holds for nonzero β v , indicating that the primary effect of frame-dragging on polarization does not depend on the orbital speed of the accreting material.…”
Section: A Direct Imagementioning
confidence: 99%
See 2 more Smart Citations
“…which holds in the limit where B eq → 0, even though (42) will not be well-defined. One can also show that this relation holds for nonzero β v , indicating that the primary effect of frame-dragging on polarization does not depend on the orbital speed of the accreting material.…”
Section: A Direct Imagementioning
confidence: 99%
“…Like the approximation (42) for the direct image, (45) holds for any magnetic field configuration and boost parameter. The correction sin −1 (a/b c ) is analogous to the "gravitational Faraday rotation" in the indirect image, thus extending the work of [46][47][48][49][50][51] to the strongly lensed regime.…”
Section: B Subimagesmentioning
confidence: 99%
See 1 more Smart Citation
“…For an emitter in a circular orbit of the extremal Kerr black hole, it was found that about 54.64% of photons escape to infinity in the limit where the orbital radius arbitrarily approaches the innermost stable circular orbit radius [7], which coincides with the horizon radius. Furthermore, the analytical value of the probability is recently found by use of the technique of the near-horizon geometry of the extremal Kerr [8]. In this case, the relativistic boost due to the source's proper motion causes such an increase in the escape probability and also the Doppler blueshift exceeding the gravitational redshift [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the escape probability of photons emitted isotropically from an emitter orbiting a circular geodesic near a Kerr black hole was shown to be more than 50% for an arbitrary black hole spin parameter and an arbitrary orbital radius [3,4]. Furthermore, depending on the direction of the emission, the Doppler shift cancels the gravitational redshift, and as a result, the signals can reach a distant observer in observable bands [3,5,6].…”
Section: Introductionmentioning
confidence: 99%